Venous thromboembolism following pegaspargase in adults receiving antithrombin supplementation. Issue 9 (28th July 2020) - Freyer, Craig W.; Carulli, Alison; Ganetsky, Alex; Hughes, Mitchell E.; Krause, Tracy M.; Timlin, Colleen; Frey, Noelle V.; Gill, Saar I.; Hexner, Elizabeth O.; Loren, Alison W.; Mangan, James K.; Martin, Mary Ellen; et al.
Abstract: Pegaspargase (PEG) increases venous thromboembolism (VTE) in acute lymphoblastic leukemia (ALL) potentially due to depletion of anticoagulation factors, including antithrombin (AT). The benefit and cost of AT supplementation in adults is unclear. We aimed to characterize VTE incidence and risk factors following AT and determine the characteristics and costs of supplementation. Fifty-three adults received PEG and AT. VTE occurred in 21% (grade ≥3 8%). T cell ALL and patients receiving prednisone during induction were at highest risk. Repeat AT levels post supplementation were subtherapeutic forty-four percent of the time. A median of 18 days elapsed between PEG and two sequential therapeutic AT levels despite supplementation. Patients received a median of 2 AT doses per PEG dose at a median cost of $11, 145. VTE remains common in adults despite AT supplementation. More aggressive AT supplementation may reduce VTE but warrant prospective evaluation given the significant cost.